The effect of environmental stressors on growth in fish and its endocrine control - Canosa, Luis Fabián; Bertucci, Juan Ignacio (Frontiers in Endocrinology, 2023)
Fish body growth is a trait of major importance for individual survival and reproduction. It has implications in population, ecology, and evolution. Somatic growth is controlled by the GH/IGF endocrine axis and is influenced by nutrition, feeding, and reproductive-regulating hormones as well as abiotic factors such as temperature, oxygen levels, and salinity. Global climate change and anthropogenic pollutants will modify environmental conditions affecting directly or indirectly fish growth performance. In the present review, we offer an overview of somatic growth and its interplay with the feeding regulatory axis and summarize the effects of global warming and the main anthropogenic pollutants on these endocrine axes.